Actors of proving in the pre-trial investigation stage: issues of updated identification and classification - Zinkovskyy, I. P. (Аналітично-порівняльне правознавство, 2025)
The article examines the list and classification of actors of proving in general and in pre-trial investigation. It notes the existence of a narrow and broad approach to actors of proving and analyses the criteria used to form narrow approaches to the list of actors of criminal procedural proving. Additional arguments are provided that a broad approach to actors of proving in pre-trial investigations is more logical. After all, the implementation of pre-trial investigation tasks is impossible without evidence. Evidence manifests itself in a number of elements that are not identical in content: for example, the collection and verification of evidence is both a practical and analytical activity, while evaluation is exclusively analytical. The list of means of collecting evidence is quite broad, and each means has its own specifics of implementation and rules for involving various participants in criminal proceedings. All these activities are aimed at forming, as a result, a set of relevant, admissible and reliable evidence sufficient for making procedural decisions. Therefore, an objective criterion for determining whether a participant is the actor of proving is whether their participation affects the relevance and/or admissibility of evidence. It has been concluded that the actors of proving in pre-trial investigation are those subjects of the pre-trial investigation stage whose participation affects the relevance and/or admissibility of evidence. According to this criterion, the classification of actors of proving for pre-trial investigation is as follows: agencies and persons who have authority and who perform the duty of proving; agencies and persons who have authority and who bear the burden of proving; persons who do not have authority and who bear the burden of proving; persons whose activities involve the right to initiate evidence; persons who are a source of general evidentiary information; persons who are a source of evidentiary information as bearers of special knowledge; persons who contribute to ensuring the admissibility of evidence.